Dioecious Silene latifolia plants show sexual dimorphism in the vegetative stage - Zluvova, Jitka; Zak, Jiri; Janousek, Bohuslav; Vyskot, Boris (Bmc plant biology, 2010)
BACKGROUND: Prior to this study, no differences in gene expression between male and female dioecious plants in the vegetative state had been detected. Among dioecious plants displaying sexual dimorphism, Silene latifolia is one of the most studied species. Although many sexually dimorphic traits have been described in S. latifolia, all of them are quantitative, and they usually become apparent only after the initiation of flowering. RESULTS: We present RT-PCR-based evidence that in S. latifolia, sexual dimorphism in gene expression is present long before the initiation of flowering. We describe three ESTs that show sex-specific (two male specific and one female specific) transcription at the rosette stage before the first flowering season. CONCLUSIONS: To our knowledge, this study provides the first molecular evidence of early pre-flowering sexual dimorphism in angiosperms.
Keywords: polymerázová řetězová reakce s reverzní transkripcí; sekvenční analýza DNA; Sequence Analysis, DNA; Silene; exprimované sekvenční adresy; stanovení celkové genové exprese; Reverse Transcriptase Polymerase Chain Reaction; Gene Expression Profiling; Gene Expression Regulation, Plant; pohlavní dimorfismus; Phylogeny; fylogeneze; Sex Characteristics; DNA rostlinná; regulace genové exprese u rostlin; DNA, Plant; Expressed Sequence Tags